Australian Animation An International History - Torre, Dan (Springer International Publishing, 2018)
This book provides the most comprehensive history and analysis of Australian animation published to date. Spanning from the 1910s to the present day, it explores a wide-range both of independent animation, and of large-scale commercial productions. Presented within a uniquely international context, it details the frequent links between Australian animation and overseas productions. New perspectives and original information are offered on a variety of international subjects such as: Felix the Cat, the Australian Hanna-Barbera studios, and the Australian Walt Disney studios. Drawing on both extensive archival research and original interviews this book illuminates, for the first time, the breadth and richness of Australia's animation history.